2016
DOI: 10.1016/j.toxrep.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a controlled food-chain mediated exposure to cadmium and arsenic on oxidative enzymes in the tissues of rats

Abstract: ObjectiveThe present study aims to investigate the effect of cadmium and arsenic through a controlled food chain on the activities of some oxidative enzymes (Sulphite oxidase SO, Aldehyde oxidase AO, Monoamine oxidase MO and Xanthine oxidase, XO) in the liver, kidney, testes, heart and brain of rats.Materials and methodsFish (the first trophic level) were exposed to both metals (singly and in mixture) using cadmium chloride (CdCl2) as the source of cadmium and arsenic trioxide (AS2O3) as the source of arsenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…The results of the present study revealed that the animals exposed to Cd through intraperitoneal injections showed loss in the body weight when compared with control rats ( Table 1). This supports the observations reported 28,29 both As and Cd decreased body weight gain and food utilization and that these effects were more pronounced for the mixture. Available reports 30,31,32 also indicate that long term exposure to arsenic and cadmium could lead to significant reduction in body weights.…”
Section: Nasupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study revealed that the animals exposed to Cd through intraperitoneal injections showed loss in the body weight when compared with control rats ( Table 1). This supports the observations reported 28,29 both As and Cd decreased body weight gain and food utilization and that these effects were more pronounced for the mixture. Available reports 30,31,32 also indicate that long term exposure to arsenic and cadmium could lead to significant reduction in body weights.…”
Section: Nasupporting
confidence: 93%
“…It was shown that reduction of body weight can be used as an important indicator for the deterioration of rat general health status. Cd and As inhibitory effect on digestive and absorption enzymes 36, 37 may also account for the decreased in weight of rats as observed 28 . In addition to above findings, in our results we have also find that the administration of α-tocopherol along with Cd shows its reversal effect on the above mentioned brain enzymes and body weights respectively.…”
Section: Namentioning
confidence: 83%
“…Cadmium possesses cytotoxic, carcinogenic, and mutagenic properties (Du et al, 2015). It causes hepatotoxicity and nephrotoxicity by acute administration (Ezedom and Asagba, 2016). Kidneys are accepted to be the most target organ of Cd toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The results in testes differed from those in the liver and kidneys, possibly because the testes have a specific blood testicular barrier; in addition, cadmium cannot easily enter the testes and the organizational structure of different cells may have led to different reactions caused by cadmium. Ezedom and Asagba (2016) reported that the activities of oxidative enzymes increased after rats were exposed to cadmium for one month (P<0.05). This finding may be because the level of cadmium was still at a low accumulated state after the 1 month exposure.…”
Section: Discussionmentioning
confidence: 99%